BRIGHT STUDENTS IN ISLAMIC PRIMARY SCHOOL FROM LOW INCOME FAMILY - Ahmad Juhaidi; Analisa Fitria; Noor Hidayati; Ahmad Wafa Nizami; Hidayat Ma'ruf; Nuril Huda; M. Noor Fuady (Khazanah: Jurnal Studi Islam dan Humaniora, 2022)
Learning is influenced by resources, context, and student input. High-achieving students who come from underprivileged families have supportive social capital to make up for the low financial and human capital in their families. The question addressed in this article is how to increase social capital in low-income families. This is a qualitative study. Data was collected by interviewing 63 informants, consisting of 28 parents and 35 high-achieving Islamic primary school (madrasah ibtidaiyah and madrasah tsanawiyah) student from underprivileged families in South Kalimantan.The study's findings indicate that trust in the family is unable to emerge and grow as a result of various statements and treatments of parents and other family members toward children. These statements and actions are reflected in parental concern, feelings of security, honesty and integrity, openness, reliability, and competence in the family. Expectations in poor families are relatively unsupportive. The general trend among poor families is that they have low expectations for the future. But hope will grow if parents have broad insights and views. Relationships between generations are built through the togetherness of parents and children and the communication and joint activities that are often carried out between family members. Communication is the most basic thing in building social capital in the family.